Victimology Review Of Victims Of Criminal Acts Of Destruction Of Goods (Case Study Decision Number: 247/Pid.B/2023/PN.Grt) - Prawitasari, Nining Yurista; Dharmawi, Muhammad Zulkarnaen; Sifah Faujiah (Dinasti Research, 2026)
The method for research uses normative juridical concepts. Protection in Law no. 13 of 2006 is interpreted as all efforts to fulfill rights and assistance to provide a sense of security to witnesses and/or victims which must be implemented by LPSK or other institutions in accordance with the provisions of this Law. The important role of witnesses and victims in bringing light to a criminal case means it is also important to provide protection for these witnesses and victims. In terms of victimology, victims are seen as very important in resolving cases (judge decisions), because victims are people who play a direct role when a crime occurs. Then there are protection efforts and rights provided by Victimology to victims. Legal protection for victims in Victimology studies is legal protection in the form of restitution and compensation, counseling protection and legal aid. Protection of crime victims is part of the legal protection of Indonesian citizens. The victim's right to justice is a human right of every person who has the right to support, recognition, protection and fair treatment as well as ensuring the supremacy of law and equal treatment before the law.